Ultrasound screening for cystic echinococcosis of school-age children in endemic areas of Chile: A pilot cross-sectional study towards integration in the Regional Program for the Elimination of Cystic Echinococcosis 2020-2029. - Cristian A Alvarez Rojas; Tommaso Manciulli; Francesca Tamarozzi; Michele Spinicci (PLoS Neglected Tropical Diseases)
Background Cystic echinococcosis (CE) is a public health problem in livestock-breeding areas, including Chile, which adhered to the Pan American Health Organization Regional Program for the Elimination of CE 2020-2029. Abdominal ultrasound (US) screening of school-aged children (SAC) in high-risk areas is envisaged by the Action Plan for Control, Monitoring and Prevention of CE of the Ministry of Health (MoH) of Chile. We implemented pilot US screening and estimated CE prevalence in SAC in three municipalities prioritized by the MoH, to inform about the feasibility of targeting this age group within the activities of the Action Plan. Methodology/principal findings A cross-sectional US screening was carried out in SAC (6-14 years) in Río Hurtado (Coquimbo region), Paillaco (Los Ríos), and Chile Chico (Aysén) municipalities. CE was diagnosed according to the WHO-IWGE recommendations. A total of 873 SAC were screened over 10 working days, with excellent participation (81-93%). Three children had hepatic CE cysts (3/873; 0.3%); the highest prevalence was found in Chile Chico (0.6%, 95% CI 0.2%-2.2%). Conclusions/significance US screening in SAC is technically feasible in Chile. While prevalence of CE in SAC might be too low to allow school-based monitoring and evaluation of a structured control program, US screening in SAC could allow early case-finding and support the implementation of control measures around new diagnoses.